2022
DOI: 10.1002/anie.202213053
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cytochrome P450 AbyV in the Final Stages of Abyssomicin C Biosynthesis

Abstract: Abyssomicin C and its atropisomer are potent inhibitors of bacterial folate metabolism. They possess complex polycyclic structures, and their biosynthesis has been shown to involve several unusual enzymatic transformations. Using a combination of synthesis and in vitro assays we reveal that AbyV, a cytochrome P450 enzyme from the aby gene cluster, catalyses a key latestage epoxidation required for the installation of the characteristic ether-bridged core of abyssomicin C. The X-ray crystal structure of AbyV ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…P450s are renowned for their remarkable versatility as biocatalysts, capable of catalyzing a wide range of reactions and processing a variety of substrates [ 35 36 ]. They effectively recognize different structural types, including aromatic compounds, polyketides, terpenes, peptides, and carbohydrates [ 37 40 ]. To investigate the substrate spectrum of CavA more closely, eight compounds were chosen for this study ( Figure 4a ).…”
Section: Resultsmentioning
confidence: 99%
“…P450s are renowned for their remarkable versatility as biocatalysts, capable of catalyzing a wide range of reactions and processing a variety of substrates [ 35 36 ]. They effectively recognize different structural types, including aromatic compounds, polyketides, terpenes, peptides, and carbohydrates [ 37 40 ]. To investigate the substrate spectrum of CavA more closely, eight compounds were chosen for this study ( Figure 4a ).…”
Section: Resultsmentioning
confidence: 99%
“…The role of AbyV, a P450 enzyme from the biosynthetic pathway of abyssomicin C 28 , an inhibitor of bacterial folate metabolism, has been revealed. 26 The synthesis of intermediates, feeding studies, in vitro assays and X-ray crystallography have shown that AbyV catalyses a late-stage epoxidation, which leads to the formation of the ether-bridged skeleton of abyssomicin C. Structural mining of the marine actinomycete Nocardiopsis species HB-J378 has led to the isolation of novel polycyclic aromatic polyketides, such as nocardiopsistin D 29 , which showed significant antimicrobial activity. 27 Sequencing of the HB-J378 genome and bioinformatic analysis revealed a typical type II polyketide gene cluster and NcdP, an enzyme with a high level of homology to flavin-dependent halogenases and which may be responsible for the bromination step.…”
mentioning
confidence: 99%
“…The structures in Figure 2 exemplify distinctive marine-derived antibacterials. The abyssomicin family of macrolactones (more than thirty spirotetronate structures, exemplified here by abyssomicin C) is encountered as secondary metabolites of marine Streptomyces [ 49 , 50 , 51 , 52 , 53 , 54 ]. The abyssomicins have attracted extensive synthetic (notably, evaluation of the property of many members of this family, including abyssomicin C, to show room-temperature atropisomers) and biosynthetic studies.…”
Section: Do Marine Organisms Biosynthesize Exceptional Inhibitors Of ...mentioning
confidence: 99%